1989
DOI: 10.1159/000234990
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Effect of Suspended Particulate Matter on the IgE Antibody Production in Mice

Abstract: Suspended particulate matter (SPM), suspended in the polluted environmental atmosphere, are perpetually inhaled into the human body and are considered to have profound effects on human health. This study investigated the enhancing effect of SPM on the IgE antibody production in mice. The IgE antibody responses in mice immunized with intranasal administration of ovalbumin (OA) plus SPM at 3-week intervals were higher than responses in the animals immunized with OA alone. When the dose of OA administered as an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
1

Year Published

1991
1991
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(34 citation statements)
references
References 7 publications
2
31
0
1
Order By: Relevance
“…Guinea pigs exposed to sulfur dioxide can develop allergic respiratory disorders (31) and increased antibody responses to allergens (32). Intranasal exposure of mice to DEP increases IgE antibody but not the IgG response to ovalbumin (8,9). Similarly, rats and human exposed to tobacco smoke, which contains PAH such as benzo(a)pyrene also found in DEP, have increased serum IgE (33).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Guinea pigs exposed to sulfur dioxide can develop allergic respiratory disorders (31) and increased antibody responses to allergens (32). Intranasal exposure of mice to DEP increases IgE antibody but not the IgG response to ovalbumin (8,9). Similarly, rats and human exposed to tobacco smoke, which contains PAH such as benzo(a)pyrene also found in DEP, have increased serum IgE (33).…”
Section: Discussionmentioning
confidence: 99%
“…Simultaneous administration of DEP increased IgE production to bystander antigens such as ovalbumin and Japanese cedar pollen when injected intraperitoneally (7,9). In addition, intranasal administration of DEP caused an increase in the IgE but not the IgG response (8,9). Previous reports have demonstrated that some PAH can have direct effects on lymphocytes, both T cells (10) and on B cells (11).…”
Section: Introductionmentioning
confidence: 95%
“…Furthermore, daily inhalation of DEPs may enhance the allergen response, possibly by increased local expression of proin¯amma-tory cytokines such as IL-5 and GM-CSF [67]. In one study, increased IgE production was also seen in mice after intranasal administration of suspended particulate matter (SPM) together with OA at 3-week intervals for a period of 21 weeks [68].…”
Section: In Vivo Studiesmentioning
confidence: 99%
“…Intraperitoneal injection of DEPs has been reported to increase the IgE response to ovalbumin and to Japanese cedar pollen (52,53). DEPs inoculated by the intranasal route act as an adjuvant activity for IgE production in mice (54).…”
Section: Mechanisms Of Diesel Exhaust-inducedmentioning
confidence: 99%
“…Diesel exhaust particles have been shown to adsorb several antigens, such as ovalbumin and the grass pollen major allergen Lolp-1, onto their surface (52,64) and, therefore, act as potential carriers of allergens, increasing their deposition in the respiratory tract. Thus, DEPs not only enhance the antigenicity of the allergen (65) but also increase the allergen dose reaching the lungs.…”
Section: Mechanisms Of Diesel Exhaust-inducedmentioning
confidence: 99%